STRATEGI PEMASARAN PEMBIAYAAN PRA-PENSIUN DAN PENSIUN DI BSI KC LUBUK PAKAM - Lisa Qamara; Ahmad Syakir (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze the marketing strategies implemented by Bank Syariah Indonesia (BSI) KC Lubuk Pakam in marketing pre-retirement and retirement financing products. This research uses a qualitative method with data collection through interviews, observation, and documentation. The results showed that BSI KC Lubuk Pakam uses a marketing mix (7P) which includes product, price, promotion, place, people, processes, and physical evidence. Supporting factors for the marketing strategy are product flexibility and collaboration with various agencies. Inhibiting factors include the lack of utilization of social media and competition with other banks. This research provides recommendations to increase promotion through social media and expand collaboration with various parties.